Geosite Assessment and Communication: A Review - Pasquaré Mariotto, F; Drymoni, K; Bonali, FL; Tibaldi, A; Corti, N; Oppizzi, P (Resources, 2023)
This work is aimed at reviewing the current state of the art in geosite selection, assessment, and communication. We first highlight the main papers that have defined paramount concepts such as geodiversity, geoheritage, and geosites. We then delve into the theoretical principles and guidelines that have been proposed over the last twenty years by researchers who have thoroughly illustrated how to individuate and assess geosites. In doing so, we illustrate notable field examples of applications of qualitative and quantitative assessments of geosites in places such as Serbia, India, Iceland, Ecuador, Sardinia (Italy), Egypt, Tasmania (Australia), and Brazil. The third part of this work is dedicated to illustrating a list (by no means exhaustive) of works that have tried to come up with innovative tools, strategies, and solutions to promote and communicate geosites. From our work, it appears that geosites can be extremely effective as fully fledged outreach tools capable of bridging the gap between Earth science and the lay public.